Misoprostol as a Drug in Prophylaxis And Management of Postpartum Haemorrhage (Journal of Chittagong Medical College Teachers' Association, 2019)
Background: PPH is a single largest and leading cause of maternal mortality & severe morbidity in developing countries. A drug is needed which should be effective, cheap, safe, does not need refrigeration and that can be easily administered by untrained person. Misoprostol is the drug that fulfills these requirements. So this study is designed to evaluate the efficacy of Misoprostol in prophylaxis & management of PPH. Materials and methods: This observational study was carried out in the department of Obstetrics and Gynecology of Bangabandhu Memorial Hospital, Chattogram, during the period January to June, 2013. Total 168 pregnant women who were at term and expected to have a vaginal delivery were taken for this study. Results: The median length of the 3rd stage of labour was 8.8 minutes. 11 women (6.54%) required a manual removal of the placenta and 23 patients (13.69%) needed further therapeutic oxytocin to control bleeding. In 145 cases (86.30%) additional oxytocic was not required, about 93.45% cases placenta was expelled out easily by active management of 3rd stage. There was a drop in Hb and haematocrit concentration after delivery, which was statistically significant. An upward trend was (>0.11°F) noticed regarding temperature after delivery. Conclusion: Misoprostol is effective for prevention and management of postpartum haemorrhage, & can consider as a good alternative to other conventional oxytocic drugs.JCMCTA 2019 ; 30 (1) : 47-50